Pharmacist-led medicines optimisation clinic for implantable cardiac device patients. (29th July 2021) - Patel, M; Fhadil, S; Zemrak, F; Wright, P; Rochford, C; Jones, S; Earley, M; Antoniou, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Cardiac implantable electronic devices (CIED) enhance detection of atrial fibrillation (AF), providing a comprehensive measure of AF burden. Patients with device-detected AF are usually referred for anticoagulation to their local anticoagulation clinic or General Practitioner (GP), which often delays time to initiation, potentially increasing the risk of stroke. In addition, AF is associated with increased risk of cardiovascular disease and mortality. Optimising blood pressure, cholesterol and lifestyle choices can significantly reduce the risk of cardiovascular disease and associated mortality in these patients. Purpose: To develop and evaluate an innovative pathway to allow Specialist Cardiac Pharmacists to promptly assess and initiate anticoagulation in patients with device-detected AF, and additionally address risk factors for prevention of cardiovascular disease. Methods: As part of a quality improvement initiative, a pathway was developed where patients with AF identified on CIED who require anticoagulation are referred for assessment and management to a pharmacist-led optimisation clinic. Specialist Cardiac Pharmacists contact patients within 5 days of referral to discuss and initiate or optimise treatment for AF, blood pressure, cholesterol and lifestyle choices. Patients deemed inappropriate for anticoagulation were referred back to the medical team for further assessment. All patients received a follow-up telephone consultation at 4-6 weeks to assess tolerability, adherence and response to treatment. Results: Between September 2020 and February 2021, 22 patients were referred to the optimisation clinic. Mean age was 74.32 +/- 12.34 years and 77% were men. Mean CHA2DS2VASc was 3.4 +/- 0.8 and mean HASBLED was 1.2 +/- 0.6. The average time from referral to anticoagulation was 3 days compared to 4 weeks prior to implementation of the pathway. All patients were assessed and appropriately anticoagulated, whereas approximately 15% of patients were still not anticoagulated at 3 months prior to implementation of the pathway despite referral to their local clinic. All patients had their blood pressure and cholesterol reviewed, which were optimised in 23% and 41% of patients respectively. All patients confirmed adherence and suffered no adverse effects on follow-up. Conclusion(s): We report the safe and successful implementation of a pharmacist-led medicines optimisation clinic. This has significantly reduced time to anticoagulation without compromising safety, as well as assuring all patients are appropriately anticoagulated. In addition, over half of patients required blood pressure and/or cholesterol optimisation to reduce the risk of cardiovascular disease, a service not previously provided for this cohort of patients.